LAW ENFORCEMENT AGAINST PALM OIL THEFT - Minggu, Sumber Horas; DM, M. Yusuf; Pardede, Rudi (JILPR Journal Indonesia Law and Policy Review, 2025)
Local governments and law enforcement agencies must promote legal education, improve the economic conditions of nearby communities, and strengthen security systems in areas vulnerable to theft. In this way, law enforcement can be more balanced: ensuring legal certainty, providing protection to victims, and acknowledging the humanitarian aspects concerning offenders who steal out of economic necessity. The aim of this study is to analyze Law Enforcement Against the Criminal Act of Palm Oil Theft in the Jurisdiction of the Bengkalis Police, to examine the obstacles to enforcement, and to identify efforts to overcome these obstacles. The method used in this research is sociological legal research. Based on the research findings, law enforcement against palm oil theft in the Bengkalis jurisdiction has not been effectively implemented. This is evidenced by the increasing frequency of palm oil theft cases within short time intervals. Although the police have taken various repressive measures, these crimes continue to recur and even tend to escalate. The public has become aware of how to circumvent legal repercussions, particularly regarding the threshold of financial loss stipulated in Supreme Court Regulation (Perma) Number 2 of 2012, which states that theft causing losses below Rp2,500,000 can be classified as a minor offense (tindak pidana ringan, or tipiring). Many offenders intentionally limit the amount of fresh fruit bunches (FFB) stolen to keep the value below this threshold. This tactic is deliberately used to avoid full criminal prosecution or harsher penalties. Obstacles in enforcing the law against palm oil theft in the Bengkalis region include: A lack of deterrent effect due to lenient penalties, Difficulty in proving the crime and calculating actual losses, Manipulation of stolen goods’ value by offenders, Socio-economic challenges faced by the surrounding communities.